New insights into CAR T cell-mediated killing of tumor cells - Espie, David; Donnadieu, Emmanuel (Frontiers in Immunology, 2022)
Adoptive transfer of T cells genetically engineered to express chimeric antigen receptors (CAR) has demonstrated striking efficacy for the treatment of several hematological malignancies, including B-cell lymphoma, leukemia, and multiple myeloma. However, CAR T-cell efficacy has been very limited in most solid tumors. In this context, it is of paramount importance to understand the determinants that condition CAR T-cell success versus failure. To control tumor growth, CAR T cells need to form conjugates with their targets via the assembly of an immunological synapse. Here, we review recent advances showing that the adhesion between CAR T cells and cancer cells from solid tumors strengthens over time in an IFNγ- and ICAM-1-dependent manner, resulting in CAR T cell-mediated killing. We discuss how these findings can be exploited to increase the efficacy of the CAR T-cell strategy against solid tumors.